2019
DOI: 10.1016/j.bpj.2019.10.037
|View full text |Cite
|
Sign up to set email alerts
|

How Heterogeneity in Glucokinase and Gap-Junction Coupling Determines the Islet [Ca2+] Response

Abstract: Understanding how cell subpopulations in a tissue impact overall system function is challenging. There is extensive heterogeneity among insulin-secreting b-cells within islets of Langerhans, including their insulin secretory response and gene expression profile, and this heterogeneity can be altered in diabetes. Several studies have identified variations in nutrient sensing between b-cells, including glucokinase (GK) levels, mitochondrial function, or expression of genes important for glucose metabolism. Subpo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 69 publications
(111 reference statements)
0
39
0
1
Order By: Relevance
“…Experimental evidence indicates that within the intact islet there exists 10-20% variation in metabolic activity [37]. Previous modelling studies have represented beta cell heterogeneity as a continuous distribution with 10-25% variation in GK activity and metabolic activity, which is sufficient to model the impact of electrical coupling and heterogeneity within the islet [29,[34][35][36]. However, recent experimental evidence has suggested that small β -cell subpopulations with elevated metabolic activity or GK expression are present within the islet and may disproportionately drive elevated [Ca 2+ ] [29,30].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Experimental evidence indicates that within the intact islet there exists 10-20% variation in metabolic activity [37]. Previous modelling studies have represented beta cell heterogeneity as a continuous distribution with 10-25% variation in GK activity and metabolic activity, which is sufficient to model the impact of electrical coupling and heterogeneity within the islet [29,[34][35][36]. However, recent experimental evidence has suggested that small β -cell subpopulations with elevated metabolic activity or GK expression are present within the islet and may disproportionately drive elevated [Ca 2+ ] [29,30].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent studies have demonstrated that heterogeneity plays a physiological role in regulating insulin release within the islet [29,30,35]. Previously, using computational models and experimental systems, we demonstrated that a large minority (close to 50%) of metabolically active β -cells were necessary to maintain the activity of the islet [35]. In contrast to this, experimental and theoretical studies have suggested that small (~10%) highly functional subpopulations may be required to maintain whole islet electrical dynamics [30,41].…”
mentioning
confidence: 81%
See 3 more Smart Citations